Kangxianling decoction prevents renal fibrosis in rats with 5/6 nephrectomy and inhibits Ang II-induced ECM production in glomerular mesangial cells - Jing Ji; Pengyu Tao; Liqun He (Elsevier, 2019)
Renal fibrosis is a common pathological change in all stages of kidney disease. Kangxianling decoction was widely used in patients with chronic kidney disease, which could improve symptoms such as poor appetite, edema, and fatigue. However, its effect on renal fibrosis remains to be studied. In this study, we investigated its effects on renal fibrosis in a rat model of 5/6 Nephrectomy (5/6 N) in vivo and in angiotensin II (Ang II)-treated rat glomerular mesangial cells (HBZY-1) in vitro. Our data showed that 5/6 N induced renal fibrosis and combined with the activation of JNK signaling, the upregulation of transforming growth factor-β (TGF-β), collagen I (Col-I) and fibronectin (FN). The administration of kangxianling decoction inhibited the activation of JNK signaling and attenuated the deposition of extracellular matrix (ECM) proteins in damaged kidneys. In HBZY-1 cells, Ang II increased the protein expression of Col-I and FN. It also activates JNK signaling and TGF-β in a time-dependent manner. Treatment of the HBZY-1 cells with kangxianling decoction blocked Ang II-induced JNK activation and ECM overproduction. Our results indicated that Kangxianling Decoction could reduce renal fibrosis, accompanied by inhibiting the production of ECM proteins and JNK, along with downregulation of TGF-β, Ang II. Keywords: Kangxianling decoction, Renal fibrosis, Angiotensin II, ECM, Transforming growth factor-β